A pilot study of the comparative efficacy of 100 Hz magnetic seizure therapy and electroconvulsive therapy in persistent depression. Issue 5 (12th January 2018) - Fitzgerald, Paul B.; Hoy, Kate E.; Elliot, David; McQueen, Susan; Wambeek, Lenore E.; Chen, Leo; Clinton, Anne Maree; Downey, Glenn; Daskalakis, Zafiris J.
Abstract : Background: Magnetic seizure therapy (MST) is a novel brain stimulation technique that uses a high‐powered transcranial magnetic stimulation device to produce therapeutic seizures. Preliminary MST studies have found antidepressant effects in the absence of cognitive side effects but its efficacy compared to electroconvulsive therapy (ECT) remains unclear. The aim of this study was to investigate the therapeutic efficacy and cognitive profile of MST compared to standard right unilateral ECT treatment. Methods: Thirty‐seven patients completed a course of at least nine ECT or MST treatments in a randomized double‐blind protocol. Assessments of depression severity and cognition were performed before and after treatment. Results: No difference in the antidepressant effectiveness between the treatments was seen across any of the clinical outcome measures, although the overall response rates in both groups were quite low. In regards to cognition, following MST there were significant improvements in tests of psychomotor speed, verbal memory, and cognitive inhibition, with no reductions in cognitive performance. Following ECT there was significant improvement in only one of the cognitive inhibition tasks. With respect to the between‐group comparisons, the MST group showed a significantly greater improvement on psychomotor speed than ECT. Conclusions: MST showed similar efficacy to right unilateral ECT in patients with treatment‐resistant depression without cognitive side effects but in a sample that was only of sufficient size to demonstrate relatively large differences in response between the two groups. Future research should aim to optimize the methods of MST administration and compare its efficacy to ECT in large randomized controlled trials.